2021
DOI: 10.1001/jamasurg.2021.0265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Nature of Sexist and Racial/Ethnic Microaggressions Against Surgeons and Anesthesiologists

Abstract: Workplace mistreatment can manifest as microaggressions that cause chronic, severe distress. As physician burnout becomes a global crisis, quantitative research to delineate the impact of microaggressions is imperative.OBJECTIVES To examine the prevalence and nature of sexist and racial/ethnic microaggressions against female and racial/ethnic-minority surgeons and anesthesiologists and assess the association with physician burnout. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional survey evaluated microagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 21 publications
1
80
0
Order By: Relevance
“…Discrimination was also associated with anxiety and depression in a study including nurses in London [35]. The negative effects of discrimination on mental health may be more pronounced for female HCWs of color; for example, one study found that female HCWs of color who reported both racial and gender discrimination were more likely to experience burnout compared with male HCWs of color [7]. However, our study did not find a significant interaction effect of race, gender, and discrimination on mental health outcomes, perhaps due to the relatively small proportions of HCWs of color in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrimination was also associated with anxiety and depression in a study including nurses in London [35]. The negative effects of discrimination on mental health may be more pronounced for female HCWs of color; for example, one study found that female HCWs of color who reported both racial and gender discrimination were more likely to experience burnout compared with male HCWs of color [7]. However, our study did not find a significant interaction effect of race, gender, and discrimination on mental health outcomes, perhaps due to the relatively small proportions of HCWs of color in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have explored experiences of racial discrimination among HCWs, those that link racism to mental health outcomes are sparse [6]. Gender discrimination is also salient within hospitals and is associated with adverse mental health outcomes; a survey study identified that 94% of female physicians experienced gender discrimination, which was associated with increased risk of burnout [7].…”
Section: Introductionmentioning
confidence: 99%
“…To progress towards health equity, members of health systems must understand our roles in combatting structural racism [3,[60][61][62][63][64]. To date, the medical profession has not fully acknowledged the history of inequality or bias in medicine and science, which includes the adverse impact of medical racism on BIPOC (Black, Indigenous and People of Color) patients; the continuing negative impact on medical professionals, including BIPOC trainees and staff; and the negative implications on healthcare's missions of patient care, education, and research [4,6,23,37,[65][66][67][68][69][70][71][72][73]. Medicine also must publicly acknowledge the unethical research that has been carried out on BIPOC individuals, such as the research-driven gynecological surgeries that J Marion Sims performed on enslaved Black women, including Anarcha Westcott, without their consent or proper anesthesia [74,75].…”
mentioning
confidence: 99%
“…13 Minorities suffer from lower matriculation rates and report experiencing increased microaggression and implicit bias. 14-17 These pervasive microaggressions significantly impact the well-being of residents and surgeons, leading to increased rates of burnout. 16,17 Minority trainees are also subject to higher levels of adverse actions such as dismissal.…”
mentioning
confidence: 99%
“…14-17 These pervasive microaggressions significantly impact the well-being of residents and surgeons, leading to increased rates of burnout. 16,17 Minority trainees are also subject to higher levels of adverse actions such as dismissal. 18…”
mentioning
confidence: 99%